Biomechanische Konditionierung von künstlichem Herzmuskelgewebe: Progressive Dehnung fördert die Differenzierung von Stammzellen zu adulten Kardiomyozyten - Lu, Kun; Seidel, Thomas; Tomasi, Roland; Hagl, Christian; Dendorfer, Andreas (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2024)
Background: Engineered heart tissue (EHT) shows promise as a replacement for damaged myocardial tissue and for understanding cardiac disease but immaturity in morphology and function remains a challenge. In this work, progressive stretching was developed and systematically evaluated as an innovative stimulation to promote EHT maturation. Methods: Ring-shaped EHT were produced from human induced-pluripotent stem cells (iPSC) and were progressively stretched at four different rates in a custom-built biomimetic tissue culture system. The self-developed bioreactor provided continuous electrical stimulation and measurement of contraction forces of eight EHT in parallel. Results: Within 3 weeks of stretch conditioning the EHT developed contractile forces comparable to human heart muscle. After this phase the EHT exhibited functional properties characteristic of human myocardium, including a positive force-frequency dependency, a significant response of contractility to alterations of preload and a physiological action potential. In addition, progressive stretching improved longitudinal growth and linear alignment of iPS cardiomyocytes as well as improved the density and maturation of sarcomeres. Conclusion: Conditioning with progressive stretching supports the mechanical, electrical, and structural maturation of engineered myocardium. This approach reduces the difference between engineered tissue and the adult human myocardium and could thus fulfil important requirements of cardiac disease modelling and myocardial tissue replacement.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Biomechanics; Maturation; Progressive stretching; Stem cell-derived myocardial tissue; Tissue engineering

Confocal microscopy-based estimation of intracellular conductivities in myocardium for modeling of the normal and infarcted heart - Greiner, Joachim; Sankarankutty, Aparna C.; Seidel, Thomas; Sachse, Frank B. (Computers in Biology and Medicine, 2022)
Ventricular arrhythmias are the leading cause of mortality in patients with ischemic heart diseases, such as myocardial infarction (MI). Computational simulation of cardiac electrophysiology provides insights into these arrhythmias and their treatment. However, only sparse information is available on crucial model parameters, for instance, the anisotropic intracellular electrical conductivities. Here, we introduced an approach to estimate these conductivities in normal and MI hearts. We processed and analyzed images from confocal microscopy of left ventricular tissue of a rabbit MI model to generate 3D reconstructions. We derived tissue features including the volume fraction of myocytes (Vmyo), gap junctions-containing voxels (Vgj), and fibrosis (Vfibrosis). We generated models of the intracellular space and intercellular coupling. Applying numerical methods for solving Poisson's equation for stationary electrical currents, we calculated normal (amyo,n), longitudinal (amyo,l), and transverse (amyo,t) intracellular conductivities. Using linear regression analysis, we assessed relationships of conductivities to tissue features. Vgj and Vmyo were reduced in MI vs. control, but Vfibrosis was increased. Both amyo,l and amyo,n were lower in MI than in control. Differences of amyo,t between control and MI were not significant. We found strong positive relationships of amyo,l with Vmyo and Vgj, and a strong negative relationship with Vfibrosis. The relationships of amyo,n with these tissue features were similar but less pronounced. Our study provides quantitative insights into the intracellular conductivities in the normal and MI heart. We suggest that our study establishes a framework for the estimation of intracellular electrical conductivities of myocardium with various pathologies.
CRIS-Team WoS Importer:2022-06-17

Confocal Microscopy-Based Estimation of Parameters for Computational Modeling of Electrical Conduction in the Normal and Infarcted Heart - Greiner, Joachim; Sankarankutty, Aparna C.; Seemann, Gunnar; Seidel, Thomas; Sachse, Frank B. (Frontiers in Physiology, 2018)
Computational modeling is an important tool to advance our knowledge on cardiac diseases and their underlying mechanisms. Computational models of conduction in cardiac tissues require identification of parameters. Our knowledge on these parameters is limited, especially for diseased tissues. Here, we assessed and quantified parameters for computational modeling of conduction in cardiac tissues. We used a rabbit model of myocardial infarction (MI) and an imaging-based approach to derive the parameters. Left ventricular tissue samples were obtained from fixed control hearts (animals: 5) and infarcted hearts (animals: 6) within 200 μm (region 1), 250-750 μm (region 2) and 1,000-1,250 μm (region 3) of the MI border. We assessed extracellular space, fibroblasts, smooth muscle cells, nuclei and gap junctions by a multi-label staining protocol. With confocal microscopy we acquired three-dimensional (3D) image stacks with a voxel size of 200 × 200 × 200 nm. Image segmentation yielded 3D reconstructions of tissue microstructure, which were used to numerically derive extracellular conductivity tensors. Volume fractions of myocyte, extracellular, interlaminar cleft, vessel and fibroblast domains in control were (in %) 65.03 ± 3.60, 24.68 ± 3.05, 3.95 ± 4.84, 7.71 ± 2.15, and 2.48 ± 1.11, respectively. Volume fractions in regions 1 and 2 were different for myocyte, myofibroblast, vessel, and extracellular domains. Fibrosis, defined as increase in fibrotic tissue constituents, was (in %) 21.21 ± 1.73, 16.90 ± 9.86, and 3.58 ± 8.64 in MI regions 1, 2, and 3, respectively. For control tissues, image-based computation of longitudinal, transverse and normal extracellular conductivity yielded (in S/m) 0.36 ± 0.11, 0.17 ± 0.07, and 0.1 ± 0.06, respectively. Conductivities were markedly increased in regions 1 (+75, +171, and +100%), 2 (+53, +165, and +80%), and 3 (+42, +141, and +60%). Volume fractions of the extracellular space including interlaminar clefts strongly correlated with conductivities in control and MI hearts. Our study provides novel quantitative data for computational modeling of conduction in normal and MI hearts. Notably, our study introduces comprehensive statistical information on tissue composition and extracellular conductivities on a microscopic scale in the MI border zone. We suggest that the presented data fill a significant gap in modeling parameters and extend our foundation for computational modeling of cardiac conduction.
EVALuna2:184907

Consecutive-Day Ventricular and Atrial Cardiomyocyte Isolations from the Same Heart: Shifting the Cost–Benefit Balance of Cardiac Primary Cell Research - Greiner, Joachim; Schiatti, Teresa; Kaltenbacher, Wenzel; Dente, Marica; Semenjakin, Alina; Kok, Thomas; Fiegle, Dominik; Seidel, Thomas; Ravens, Ursula; Kohl, Peter; Peyronnet, Rémi; Rog-Zielinska, Eva A. (Cells, 2022)
Freshly isolated primary cardiomyocytes (CM) are indispensable for cardiac research. Experimental CM research is generally incompatible with life of the donor animal, while human heart samples are usually small and scarce. CM isolation from animal hearts, traditionally performed by coronary artery perfusion of enzymes, liberates millions of cells from the heart. However, due to progressive cell remodeling following isolation, freshly isolated primary CM need to be used within 4–8 h post-isolation for most functional assays, meaning that the majority of cells is essentially wasted. In addition, coronary perfusion-based isolation cannot easily be applied to human tissue biopsies, and it does not straightforwardly allow for assessment of regional differences in CM function within the same heart. Here, we provide a method of multi-day CM isolation from one animal heart, yielding calcium-tolerant ventricular and atrial CM. This is based on cell isolation from cardiac tissue slices following repeated (usually overnight) storage of the tissue under conditions that prolong CM viability beyond the day of organ excision by two additional days. The maintenance of cells in their near-native microenvironment slows the otherwise rapid structural and functional decline seen in isolated CM during attempts for prolonged storage or culture. Multi-day slice-based CM isolation increases the amount of useful information gained per animal heart, improving reproducibility and reducing the number of experimental animals required in basic cardiac research. It also opens the doors to novel experimental designs, including exploring same-heart regional differences.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Cardiomyocyte isolation; Sarcomere shortening; Single cell; Tissue preservation

Contractility measurements for cardiotoxicity screening with ventricular myocardial slices of pigs - Shi, Runzhu; Reichardt, Marius; Fiegle, Dominik; Küpfer, Linda; Czajka, Titus; Sun, Zhengwu; Salditt, Tim; Dendorfer, Andreas; Seidel, Thomas; Bruegmann, Tobias (Cardiovascular Research, 2023)
Aims Cardiotoxicity is one major reason why drugs do not enter or are withdrawn from the market. Thus, approaches are required to predict cardiotoxicity with high specificity and sensitivity. Ideally, such methods should be performed within intact cardiac tissue with high relevance for humans and detect acute and chronic side effects on electrophysiological behaviour, contractility, and tissue structure in an unbiased manner. Herein, we evaluate healthy pig myocardial slices and biomimetic cultivation setups (BMCS) as a new cardiotoxicity screening approach. Methods and results Pig left ventricular samples were cut into slices and spanned into BMCS with continuous electrical pacing and online force recording. Automated stimulation protocols were established to determine the force-frequency relationship (FFR), frequency dependence of contraction duration, effective refractory period (ERP), and pacing threshold. Slices generated 1.3 ± 0.14 mN/mm2 force at 0.5 Hz electrical pacing and showed a positive FFR and a shortening of contraction duration with increasing pacing rates. Approximately 62% of slices were able to contract for at least 6 days while showing stable ERP, contraction duration-frequency relationship, and preserved cardiac structure confirmed by confocal imaging and X-ray diffraction analysis. We used specific blockers of the most important cardiac ion channels to determine which analysis parameters are influenced. To validate our approach, we tested five drug candidates selected from the Comprehensive in vitro Proarrhythmia Assay list as well as acetylsalicylic acid and DMSO as controls in a blinded manner in three independent laboratories. We were able to detect all arrhythmic drugs and their respective mode of action on cardiac tissue including inhibition of Na+, Ca2+, and hERG channels as well as Na+/Ca2+ exchanger. Conclusion We systematically evaluate this approach for cardiotoxicity screening, which is of high relevance for humans and can be upscaled to medium-throughput screening. Thus, our approach will improve the predictive value and efficiency of preclinical cardiotoxicity screening.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Cardiac arrhythmia; Cardiotoxicity; Drug-induced long QT syndrome; Screening; Ventricular slices

Correction to: Consecutive-Day Ventricular and Atrial Cardiomyocyte Isolations from the Same Heart: Shifting the Cost–Benefit Balance of Cardiac Primary Cell Research (Cells, (2022), 11, 2, (233), 10.3390/cells11020233) - Greiner, Joachim; Schiatti, Teresa; Kaltenbacher, Wenzel; Dente, Marica; Semenjakin, Alina; Kok, Thomas; Fiegle, Dominik; Seidel, Thomas; Ravens, Ursula; Kohl, Peter; Peyronnet, Rémi; Rog-Zielinska, Eva A. (Cells, 2024)
In the original publication [1], there was an error in the Materials and Methods Section, Sub-Section 2.3. Cell Isolation. The concentration of the digestion solution was wrong. The correct concentration appears below. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated. Tissue was then rinsed twice in wash solution 1 (each 2 mL), and further digested with Liberase TL Research Grade (concentration: 0.23 mg/mL in 2.2 mL wash solution 1 supplemented with 5 µM CaCl2; Hoffmann-La Roche, Basel, Switzerland) for up to 45 min (ventricles)/15 min (atria).
CRIS-Team Scopus Importer:2024-07-12

Correction to: Long-term functional and structural preservation of precision-cut human myocardium under continuous electromechanical stimulation in vitro (Nature Communications, (2019), 10, 1, (117), 10.1038/s41467-018-08003-1) - Fischer, Carola; Milting, Hendrik; Fein, Evelyn; Reiser, Elisabeth; Lu, Kun; Seidel, Thomas; Schinner, Camilla; Schwarzmayr, Thomas; Schramm, Rene; Tomasi, Roland; Husse, Britta; Cao-Ehlker, Xiaochun; et al. (Nature Communications, 2019)
The original version of this Article incorrectly acknowledged Elisabeth Reiser and Rene Schramm as a corresponding author. This has now been corrected in both the PDF and HTML versions of the Article.
CRIS-Team Scopus Importer:2019-05-14

Corrigendum: long-term cultivation of human atrial myocardium (Frontiers in Physiology, (2022), 13, (839139), 10.3389/fphys.2022.839139) - Klumm, Maximilian J. J.; Heim, Christian; Fiegle, Dominik; Weyand, Michael; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2023)
In the published article, there was an error in Author Contributions. The following sentence was missing. MK performed this work in (partial) fulfillment of the requirements for obtaining the degree “Dr. med.”. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2023-06-02
Keywords: calcium imaging; confocal microscopy; gene expression; human atrium; in vitro; refractory period; tissue culture

Dexamethasone prevents loss of T-tubules in primary cultured adult rat cardiomyocytes - Seidel, Thomas; Baur, T.; Volk, Tilmann (2017)
EVALuna2:214663

Effects of electro-mechanical uncouplers, hormonal stimulation and pacing rate on the stability and function of cultured rabbit myocardial slices - Baron, V.; Sommer, Sophie; Fiegle, Dominik; Pfeuffer, Ann-Katrin; Peyronnet, R.; Volk, Tilmann; Seidel, Thomas (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Recent advances have enabled organotypic culture of beating human myocardial slices that are stable for weeks. However, human myocardial samples are rare, exhibit high variability and frequently originate from diseased hearts. Thus, there is a need to adapt long-term slice culture for animal myocardium. When applied to animal cardiac slices, studies in healthy or genetically modified myocardium will be possible. We present the culture of slices from rabbit hearts, which resemble the human heart in microstructure, electrophysiology and excitation-contraction coupling. Methods: Left ventricular myocardium from New Zealand White rabbits was cut using a vibratome and cultured in biomimetic chambers for up to 7 days (d). Electro-mechanical uncoupling agents 2,3-butanedione monoxime (BDM) and cytochalasin D (CytoD) were added during initiation of culture and effects on myocyte survival were quantified. We investigated pacing rates (0.5 Hz, 1 Hz, and 2 Hz) and hormonal supplements (cortisol, T3, catecholamines) at physiological plasma concentrations. T3 was buffered using BSA. Contractile force was recorded continuously. Glucose consumption and lactate production were measured. Whole-slice Ca2+ transients and action potentials were recorded. Effects of culture on microstructure were investigated with confocal microscopy and image analysis. Results: Protocols for human myocardial culture resulted in sustained contracture and myocyte death in rabbit slices within 24 h, which could be prevented by transient application of a combination of BDM and CytoD. Cortisol stabilized contraction amplitude and kinetics in culture. T3 and catecholaminergic stimulation did not further improve stability. T3 and higher pacing rates increased metabolic rate and lactate production. T3 stabilized the response to β-adrenergic stimulation over 7 d. Pacing rates above 1 Hz resulted in progredient decline in contraction force. Image analysis revealed no changes in volume fractions of cardiomyocytes or measures of fibrosis over 7 d. Ca2+ transient amplitudes and responsiveness to isoprenaline were comparable after 1 d and 7 d, while Ca2+ transient duration was prolonged after 7 d in culture. Conclusions: A workflow for rabbit myocardial culture has been established, preserving function for up to 7 d. This research underscores the importance of glucocorticoid signaling in maintaining tissue function and extending culture duration. Furthermore, BDM and CytoD appear to protect from tissue damage during the initiation phase of tissue culture.
CRIS-Team Scopus Importer:2024-05-10
Keywords: biomimetic chambers; contractility; multicellular preparations; organotypic culture; reperfusion injury

Establishing a new cardiac toxicity screening method using pig myocardial slices - Shi, R.; Reichardt, M.; Fiegle, Dominik; Czajka, T.; Sun, Z.; Salditt, T.; Seidel, Thomas; Dendorfer, A.; Bruegmann, T. (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Glucocorticoid signaling and modulation of autophagy is involved in the preservation of the cardiomyocyte t-tubular system - Fiegle, Dominik; Abu-Khousa, M.; Seidel, Thomas; Volk, Tilmann (ACTA PHYSIOLOGICA, 2019)
CRIS-Team WoS Importer:2019-11-12

Glucocorticoids preserve the t-tubular system in ventricular cardiomyocytes by upregulation of autophagic flux - Seidel, Thomas; Fiegle, Dominik; Baur, Tim J.; Ritzer, Anne; Nay, Sandra; Heim, Christian; Weyand, Michael; Milting, Hendrik; Oakley, Robert H.; Cidlowski, John A.; Volk, Tilmann (Basic Research in Cardiology, 2019)
A major contributor to contractile dysfunction in heart failure is remodelling and loss of the cardiomyocyte transverse tubular system (t-system), but underlying mechanisms and signalling pathways remain elusive. It has been shown that dexamethasone promotes t-tubule development in stem cell-derived cardiomyocytes and that cardiomyocyte-specific glucocorticoid receptor (GR) knockout (GRKO) leads to heart failure. Here, we studied if the t-system is altered in GRKO hearts and if GR signalling is required for t-system preservation in adult cardiomyocytes. Confocal and 3D STED microscopy of myocardium from cardiomyocyte-specific GRKO mice revealed decreased t-system density and increased distances between ryanodine receptors (RyR) and L-type Ca2+ channels (LTCC). Because t-system remodelling and heart failure are intertwined, we investigated the underlying mechanisms in vitro. Ventricular cardiomyocytes from failing human and healthy adult rat hearts cultured in the absence of glucocorticoids (CTRL) showed distinctively lower t-system density than cells treated with dexamethasone (EC50 1.1 nM) or corticosterone. The GR antagonist mifepristone abrogated the effect of dexamethasone. Dexamethasone improved RyR–LTCC coupling and synchrony of intracellular Ca2+ release, but did not alter expression levels of t-system-associated proteins junctophilin-2 (JPH2), bridging integrator-1 (BIN1) or caveolin-3 (CAV3). Rather, dexamethasone upregulated LC3B and increased autophagic flux. The broad-spectrum protein kinase inhibitor staurosporine prevented dexamethasone-induced upregulation of autophagy and t-system preservation, and autophagy inhibitors bafilomycin A and chloroquine accelerated t-system loss. Conversely, induction of autophagy by rapamycin or amino acid starvation preserved the t-system. These findings suggest that GR signalling and autophagy are critically involved in t-system preservation and remodelling in the heart.
CRIS-Team Scopus Importer:2019-11-08
Keywords: Autophagy; Calcium signalling; Excitation–contraction coupling; Glucocorticoid receptor; Heart failure; Remodelling; Transverse tubular system

Isolation of human ventricular cardiomyocytes from vibratome-cut myocardial slices - Fiegle, Dominik; Volk, Tilmann; Seidel, Thomas (Journal of Visualized Experiments, 2020)
The isolation of ventricular cardiac myocytes from animal and human hearts is a fundamental method in cardiac research. Animal cardiomyocytes are commonly isolated by coronary perfusion with digestive enzymes. However, isolating human cardiomyocytes is challenging because human myocardial specimens usually do not allow for coronary perfusion, and alternative isolation protocols result in poor yields of viable cells. In addition, human myocardial specimens are rare and only regularly available at institutions with on-site cardiac surgery. This hampers the translation of findings from animal to human cardiomyocytes. Described here is a reliable protocol that enables efficient isolation of ventricular myocytes from human and animal myocardium. To increase the surface-to-volume ratio while minimizing cell damage, myocardial tissue slices 300 µm thick are generated from myocardial specimens with a vibratome. Tissue slices are then digested with protease and collagenase. Rat myocardium was used to establish the protocol and quantify yields of viable, calcium-tolerant myocytes by flow-cytometric cell counting. Comparison with the commonly used tissue-chunk method showed significantly higher yields of rod-shaped cardiomyocytes (41.5 ± 11.9 vs. 7.89 ± 3.6%, p < 0.05). The protocol was translated to failing and non-failing human myocardium, where yields were similar as in rat myocardium and, again, markedly higher than with the tissue-chunk method (45.0 ± 15.0 vs. 6.87 ± 5.23 cells/mg, p < 0.05). Notably, with the protocol presented it is possible to isolate reasonable numbers of viable human cardiomyocytes (9–200 cells/mg) from minimal amounts of tissue (<50 mg). Thus, the method is applicable to healthy and failing myocardium from both human and animal hearts. Furthermore, it is possible to isolate excitable and contractile myocytes from human tissue specimens stored for up to 36 h in cold cardioplegic solution, rendering the method particularly useful for laboratories at institutions without on-site cardiac surgery.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Biology; Calcium imaging; Cardiac excitation-contraction coupling; Cardiomyocyte isolation; Contractile myocytes; Heart failure; Human; Issue 159; Myocardial slices; Vibratome

Long-Term Cultivation of Human Atrial Myocardium - Klumm, Maximilian J.; Heim, Christian; Fiegle, Dominik; Weyand, Michael; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2022)
Organotypic culture of human ventricular myocardium is emerging in basic and translational cardiac research. However, few institutions have access to human ventricular tissue, whereas atrial tissue is more commonly available and important for studying atrial physiology. This study presents a method for long-term cultivation of beating human atrial myocardium. After written informed consent, tissues from the right-atrial appendage were obtained from patients with sinus rhythm undergoing open heart surgery with cardiopulmonary bypass. Trabeculae (pectinate muscles) prepared from the samples were installed into cultivation chambers at 37°C with a diastolic preload of 500 μN. After 2 days with 0.5 Hz pacing, stimulation frequency was set to 1 Hz. Contractile force was monitored continuously. Beta-adrenergic response, refractory period (RP) and maximum captured frequency (fmax) were assessed periodically. After cultivation, viability and electromechanical function were investigated, as well as the expression of several genes important for intracellular Ca2+ cycling and electrophysiology. Tissue microstructure was analyzed by confocal microscopy. We cultivated 19 constantly beating trabeculae from 8 patient samples for 12 days and 4 trabeculae from 3 specimen for 21 days. Functional parameters were compared directly after installation (0 d) with those after 12 d in culture. Contraction force was 384 ± 69 μN at 0 d and 255 ± 90 μN at 12 d (p = 0.8, n = 22), RP 480 ± 97 ms and 408 ± 78 ms (p = 0.3, n = 9), fmax 3.0 ± 0.5 Hz and 3.8 ± 0.5 Hz (p = 0.18, n = 9), respectively. Application of 100 nM isoprenaline to 11 trabeculae at 7 d increased contraction force from 168 ± 35 μN to 361 ± 60 μN (p < 0.01), fmax from 6.4 ± 0.6 Hz to 8.5 ± 0.4 Hz (p < 0.01) and lowered RP from 319 ± 22 ms to 223 ± 15 ms. CACNA1c (L-type Ca2+ channel subunit) and GJA1 (connexin-43) mRNA expressions were not significantly altered at 12 d vs 0 d, while ATP2A (SERCA) and KCNJ4 (Kir2.3) were downregulated, and KCNJ2 (Kir2.1) was upregulated. Simultaneous Ca2+ imaging and force recording showed preserved excitation-contraction coupling in cultivated trabeculae. Confocal microscopy indicated preserved cardiomyocyte structure, unaltered amounts of extracellular matrix and gap junctions. MTT assays confirmed viability at 12 d. We established a workflow that allows for stable cultivation and functional analysis of beating human atrial myocardium for up to 3 weeks. This method may lead to novel insights into the physiology and pathophysiology of human atrial myocardium.
CRIS-Team Scopus Importer:2022-03-25
Keywords: calcium imaging; confocal microscopy; gene expression; human atrium; in vitro; refractory period; tissue culture

Long-term functional and structural preservation of precision-cut human myocardium under continuous electromechanical stimulation in vitro - Fischer, Carola; Milting, Hendrik; Fein, Evelyn; Reiser, Elisabeth; Lu, Kun; Seidel, Thomas; Schinner, Camilla; Schwarzmayr, Thomas; Schramm, Rene; Tomasi, Roland; Husse, Britta; Cao-Ehlker, Xiaochun; et al. (Nature Communications, 2019)
In vitro models incorporating the complexity and function of adult human tissues are highly desired for translational research. Whilst vital slices of human myocardium approach these demands, their rapid degeneration in tissue culture precludes long-term experimentation. Here, we report preservation of structure and performance of human myocardium under conditions of physiological preload, compliance, and continuous excitation. In biomimetic culture, tissue slices prepared from explanted failing human hearts attain a stable state of contractility that can be monitored for up to 4 months or 2000000 beats in vitro. Cultured myocardium undergoes particular alterations in biomechanics, structure, and mRNA expression. The suitability of the model for drug safety evaluation is exemplified by repeated assessment of refractory period that permits sensitive analysis of repolarization impairment induced by the multimodal hERG-inhibitor pentamidine. Biomimetic tissue culture will provide new opportunities to study drug targets, gene functions, and cellular plasticity in adult human myocardium.
CRIS-Team Scopus Importer:2019-05-07

Optimized Conditions for Electrical Tissue Stimulation with Biphasic, Charge-Balanced Impulses - Sun, Zhengwu; Sen, Payel; Hamers, Jules; Seidel, Thomas; Dendorfer, Andreas; Kameritsch, Petra (Bioengineering, 2025)
The cultivation of excitable cells typically profits from continuous electrical stimulation, but electrochemical consequences are mostly harmful and must be minimized. The properties of the electrode materials and stimulation impulses are key. Here, we developed an easy method to analyze the electrochemical impact of biphasic, current-controlled impulses, applied via graphite electrodes, using phenol red as the redox indicator. We also tested the stimulation conditions for the long-term cultivation of myocardial tissue. The colorimetric assay was able to detect ±0.2% deviations in typical positive and negative pulse charges. Phenol red was best preserved (20% degradation over 24 h) by impulses of equivalent positive and negative charges (full charge balance), generated with either manual calibration, capacitive electrode coupling, or feedback regulation of electrode polarization. Feedback regulation established full charge balance at pre-pulse voltages of about 300 mV, but also provided the option to selectively compensate irreversible electrode reactions. Modifications to shape and timing did not affect the electrochemical effects of symmetric impulses. Charge-balanced stimulation maintained more than 80% of the contractility of porcine left ventricular myocardium after 10 days of culture, whereas disbalances of 2–4% provoked weakening and discoloration of the tissues. Active polarization regulation, in contrast to capacitive electrode coupling, reproduced the biological advantages of full charge balance.
CRIS-Team Scopus Importer:2025-04-04
Keywords: biphasic; charge balance; field stimulation; living myocardial slice; tissue culture

Physiological in vitro sacroiliac joint motion: a study on three-dimensional posterior pelvic ring kinematics - Hammer, Niels; Scholze, Mario; Kibsgard, Thomas; Klima, Stefan; Schleifenbaum, Stefan; Seidel, Thomas; Werner, Michael; Grunert, Ronny (Journal of Anatomy, 2019)
The sacroiliac joint (SIJ) is a well-known source of low back and pelvic pain, of increasing interest for both conservative and surgical treatment. Alterations in the kinematics of the pelvis have been hypothesized as a major cause of SIJ-related pain. However, definitions of both the range and the extent of physiological movement are controversial, and there are no clear baseline data for pathological alterations. The present study combined a novel biomechanical setup allowing for physiological motion of the lumbosacral transition and pelvis without restricting the SIJ movement in vitro, combined with optical image correlation. Six fresh human pelvises (81 +/- 10 years, three females, three males) were tested, with bodyweight-adapted loading applied to the fifth lumbar vertebra and both acetabula. Deformation at the lumbopelvises was determined computationally from three-dimensional image correlation data. Sacroiliac joint motion under the loading of 100% bodyweight primarily consisted of a z-axis rotation (0.16 degrees) and an inferior translation of the sacrum relative to the ilium (0.32 mm). Sacroiliac joint flexion-extension rotations were minute (< 0.02 degrees). Corresponding movements of the SIJ were found at the lumbosacral transition, with an anterior translation of L5 relative to the sacrum of -0.97 mm and an inferior translation of 0.11 mm, respectively. Moreover, a flexion of 1.82 degrees was observed at the lumbosacral transition. Within the innominate bone and at the pubic symphysis, small complementary rotations were seen around a vertical axis, accounting for -0.10 degrees and 0.11 degrees, respectively. Other motions were minute and accompanied by large interindividual variation. The present study provides evidence of different SIJ motions than reported previously when exerted by physiological loading. Sacroiliac joint kinematics were in the sub-degree and sub-millimeter range, in line with previous in vivo and in vitro findings, largely limited to the sagittal rotation and an inferior translation of the sacrum relative to the ilium. This given physiological loading scenario underlines the relevance of the lumbosacral transition when considering the overall motion of the lumbopelvis, and how relatively little the other segments contribute to overall motion.
CRIS-Team WoS Importer:2019-02-27

Preparation of Human Myocardial Tissue for Long-term Cultivation - Hamers, Jules; Sen, Payel; Merkus, Daphne; Seidel, Thomas; Lu, Kun; Dendorfer, Andreas (Journal of Visualized Experiments, 2022)
Cardiomyocyte cultivation has seen a vast number of developments, ranging from two-dimensional (2D) cell cultivation to iPSC derived organoids. In 2019, an ex vivo way to cultivate myocardial slices obtained from human heart samples was demonstrated, while approaching in vivo condition of myocardial contraction. These samples originate mostly from heart transplantations or left-ventricular assist device placements. Using a vibratome and a specially developed cultivation system, 300 µm thick slices are placed between a fixed and a spring wire, allowing for stable and reproducible cultivation for several weeks. During cultivation, the slices are continuously stimulated according to individual settings. Contractions can be displayed and recorded in real-time, and pharmacological agents can be readily applied. User-defined stimulation protocols can be scheduled and performed to assess vital contraction parameters like post-pause-potentiation, stimulation threshold, force-frequency relation, and refractory period. Furthermore, the system enables a variable pre-and afterload setting for a more physiological cultivation. Here, we present a step-by-step guide on how to generate a successful long-term cultivation of human left ventricular myocardial slices, using a commercial biomimetic cultivation solution.
CRIS-Team Scopus Importer:2022-07-01

Progressive stretch enhances growth and maturation of 3D stem-cell-derived myocardium - Lu, Kun; Seidel, Thomas; Cao-Ehlker, Xiaochun; Dorn, Tatjana; Batcha, Aarif Mohamed Nazeer; Schneider, Christine Maria; Semmler, Marie; Volk, Tilmann; Moretti, Alessandra; Dendorfer, Andreas; Tomasi, Roland (Theranostics, 2021)
Bio-engineered myocardium has great potential to substitute damaged myocardium and for studies of myocardial physiology and disease, but structural and functional immaturity still implies limitations. Current protocols of engineered heart tissue (EHT) generation fall short of simulating the conditions of postnatal myocardial growth, which are characterized by tissue expansion and increased mechanical load. To investigate whether these two parameters can improve EHT maturation, we developed a new approach for the generation of cardiac tissues based on biomimetic stimulation under application of continuously increasing stretch. Methods: EHTs were generated by assembling cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CM) at high cell density in a low collagen hydrogel. Maturation and growth of the EHTs were induced in a custom-made biomimetic tissue culture system that provided continuous electrical stimulation and medium agitation along with progressive stretch at four different increments. Tissues were characterized after a three week conditioning period. Results: The highest rate of stretch (S3 = 0.32 mm/day) increased force development by 5.1-fold compared to tissue with a fixed length, reaching contractility of 11.28 mN/mm2. Importantly, intensely stretched EHTs developed physiological length-dependencies of active and passive forces (systolic/diastolic ratio = 9.47 ± 0.84), and a positive force-frequency relationship (1.25-fold contractility at 180 min-1). Functional markers of stretch-dependent maturation included enhanced and more rapid Ca2+ transients, higher amplitude and upstroke velocity of action potentials, and pronounced adrenergic responses. Stretch conditioned hiPSC-CMs displayed structural improvements in cellular volume, linear alignment, and sarcomere length (2.19 ± 0.1 µm), and an overall upregulation of genes that are specifically expressed in adult cardiomyocytes. Conclusions: With the intention to simulate postnatal heart development, we have established techniques of tissue assembly and biomimetic culture that avoid tissue shrinkage and yield muscle fibers with contractility and compliance approaching the properties of adult myocardium. This study demonstrates that cultivation under progressive stretch is a feasible way to induce growth and maturation of stem cell-derived myocardium. The novel tissue-engineering approach fulfills important requirements of disease modelling and therapeutic tissue replacement.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Biomechanics; Engineered heart tissue; Maturation; Progressive stretch; Stem-cell-derived myocardium

Remodeling of t-system and proteins underlying excitation-contraction coupling in aging versus failing human heart - Lyu, Yankun; Verma, Vipin K.; Lee, Younjee; Taleb, Iosif; Badolia, Rachit; Shankar, Thirupura S.; Kyriakopoulos, Christos P.; Selzman, Craig H.; Caine, William; Alharethi, Rami; Navankasattusas, Sutip; Seidel, Thomas; et al. (npj Aging and Mechanisms of Disease, 2021)
It is well established that the aging heart progressively remodels towards a senescent phenotype, but alterations of cellular microstructure and their differences to chronic heart failure (HF) associated remodeling remain ill-defined. Here, we show that the transverse tubular system (t-system) and proteins underlying excitation-contraction coupling in cardiomyocytes are characteristically remodeled with age. We shed light on mechanisms of this remodeling and identified similarities and differences to chronic HF. Using left ventricular myocardium from donors and HF patients with ages between 19 and 75 years, we established a library of 3D reconstructions of the t-system as well as ryanodine receptor (RyR) and junctophilin 2 (JPH2) clusters. Aging was characterized by t-system alterations and sarcolemmal dissociation of RyR clusters. This remodeling was less pronounced than in HF and accompanied by major alterations of JPH2 arrangement. Our study indicates that targeting sarcolemmal association of JPH2 might ameliorate age-associated deficiencies of heart function.
CRIS-Team WoS Importer:2021-06-04

Ryanodine Receptor Staining Identifies Viable Cardiomyocytes in Human and Rabbit Cardiac Tissue Slices - Pfeuffer, Ann-Katrin; Küpfer, Linda; Shankar, Thirupura S.; Drakos, Stavros G.; Volk, Tilmann; Seidel, Thomas (International Journal of Molecular Sciences, 2023)
In terms of preserving multicellularity and myocardial function in vitro, the cultivation of beating myocardial slices is an emerging technique in basic and translational cardiac research. It can be used, for example, for drug screening or to study pathomechanisms. Here, we describe staining for viable cardiomyocytes based on the immunofluorescence of ryanodine receptors (RyRs) in human and rabbit myocardial slices. Biomimetic chambers were used for culture and measurements of contractile force. Fixable fluorophore-conjugated dextran, entering cells with a permeable membrane, was used for death staining. RyRs, nuclei and the extracellular matrix, including the t-system, were additionally stained and analyzed by confocal microscopy and image processing. We found the mutual exclusion of the RyR and dextran signals in cultivated slices. T-System density and nucleus size were reduced in RyR-negative/dextran-positive myocytes. The fraction of RyR-positive myocytes and pixels correlated with the contractile force. In RyR-positive/dextran-positive myocytes, we found irregular RyR clusters and SERCA distribution patterns, confirmed by an altered power spectrum. We conclude that RyR immunofluorescence indicates viable cardiomyocytes in vibratome-cut myocardial slices, facilitating the detection and differential structural analysis of living vs. dead or dying myocytes. We suggest the loss of sarcoplasmic reticulum integrity as an early event during cardiomyocyte death.
CRIS-Team Scopus Importer:2023-09-15
Keywords: cardiac tissue slices; death staining; ryanodine receptor; sarcoplasmic reticulum; viability assay

Severe T-System Remodeling in Pediatric Viral Myocarditis - Fiegle, Dominik; Schober, Martin; Dittrich, Sven; Cesnjevar, Robert; Klingel, Karin; Volk, Tilmann; Alkassar, Muhannad; Seidel, Thomas (Frontiers in Cardiovascular Medicine, 2021)
Chronic heart failure (HF) in adults causes remodeling of the cardiomyocyte transverse tubular system (t-system), which contributes to disease progression by impairing excitation-contraction (EC) coupling. However, it is unknown if t-system remodeling occurs in pediatric heart failure. This study investigated the t-system in pediatric viral myocarditis. The t-system and integrity of EC coupling junctions (co-localization of L-type Ca2+ channels with ryanodine receptors and junctophilin-2) were analyzed by 3D confocal microscopy in left-ventricular (LV) samples from 5 children with myocarditis (age 14 +/- 3 months), undergoing ventricular assist device (VAD) implantation, and 5 children with atrioventricular septum defect (AVSD, age 17 +/- 3 months), undergoing corrective surgery. LV ejection fraction (EF) was 58.4 +/- 2.3% in AVSD and 12.2 +/- 2.4% in acute myocarditis. Cardiomyocytes from myocarditis samples showed increased t-tubule distance (1.27 +/- 0.05 mu m, n = 34 cells) and dilation of t-tubules (volume-length ratio: 0.64 +/- 0.02 mu m(2)) when compared with AVSD (0.90 +/- 0.02 mu m, p < 0.001; 0.52 +/- 0.02 mu m(2), n = 61, p < 0.01). Intriguingly, 4 out of 5 myocarditis samples exhibited sheet-like t-tubules (t-sheets), a characteristic feature of adult chronic heart failure. The fraction of extracellular matrix was slightly higher in myocarditis (26.6 +/- 1.4%) than in AVSD samples (24.4 +/- 0.8%, p < 0.05). In one case of myocarditis, a second biopsy was taken and analyzed at VAD explantation after extensive cardiac recovery (EF from 7 to 56%) and clinical remission. When compared with pre-VAD, t-tubule distance and density were unchanged, as well as volume-length ratio (0.67 +/- 0.04 mu m(2) vs. 0.72 +/- 0.05 mu m(2), p = 0.5), reflecting extant t-sheets. However, junctophilin-2 cluster density was considerably higher (0.12 +/- 0.02 mu m(-3) vs. 0.05 +/- 0.01 mu m(-3), n = 9/10, p < 0.001), approaching values of AVSD (0.13 +/- 0.05 mu m(-3), n = 56), and the measure of intact EC coupling junctions showed a distinct increase (20.2 +/- 5.0% vs. 6.8 +/- 2.2%, p < 0.001). Severe t-system loss and remodeling to t-sheets can occur in acute HF in young children, resembling the structural changes of chronically failing adult hearts. T-system remodeling might contribute to cardiac dysfunction in viral myocarditis. Although t-system recovery remains elusive, recovery of EC coupling junctions may be possible and deserves further investigation.
CRIS-Team WoS Importer:2021-02-19

Structural and Functional Assessment of Human Ventricular Myocardium - Abu-Khousa, M.; Fiegle, Dominik; Dendorfer, A.; Volk, Tilmann; Seidel, Thomas (ACTA PHYSIOLOGICA, 2019)
CRIS-Team WoS Importer:2019-11-12

Synchronous force and Ca2+ measurements for repeated characterization of excitation-contraction coupling in human myocardium - Sun, Zhengwu; Lu, Kun; Kamla, Christine; Kameritsch, Petra; Seidel, Thomas; Dendorfer, Andreas (Communications Biology, 2024)
Dysfunctional Ca2+ signaling affects the myocardial systole and diastole, may trigger arrhythmia and cause transcriptomic and proteomic modifications in heart failure. Thus, synchronous real-time measurement of Ca2+ and force is essential to investigate the relationship between contractility and Ca2+ signaling and the alteration of excitation-contraction coupling (ECC) in human failing myocardium. Here, we present a method for synchronized acquisition of intracellular Ca2+ and contraction force in long-term cultivated slices of human failing myocardium. Synchronous time series of contraction force and intracellular Ca2+ were used to calculate force-calcium loops and to analyze the dynamic alterations of ECC in response to various pacing frequencies, post-pause potentiation, high mechanical preload and pharmacological interventions in human failing myocardium. We provide an approach to simultaneously and repeatedly investigate alterations of contractility and Ca2+ signals in long-term cultured myocardium, which will allow detecting the effects of electrophysiological or pharmacological interventions on human myocardial ECC.
CRIS-Team Scopus Importer:2024-03-01

The Degree of t-System Remodeling Predicts Negative Force-Frequency Relationship and Prolonged Relaxation Time in Failing Human Myocardium - Abu-Khousa, Maha; Fiegle, Dominik; Sommer, Sophie T.; Minabari, Ghazali; Milting, Hendrik; Heim, Christian; Weyand, Michael; Tomasi, Roland; Dendorfer, Andreas; Volk, Tilmann; Seidel, Thomas (Frontiers in Physiology, 2020)
The normally positive cardiac force-frequency relationship (FFR) becomes flat or negative in chronic heart failure (HF). Here we explored if remodeling of the cardiomyocyte transverse tubular system (t-system) is associated with alterations in FFR and contractile kinetics in failing human myocardium. Left-ventricular myocardial slices from 13 failing human hearts were mounted into a biomimetic culture setup. Maximum twitch force (F), 90% contraction duration (CD90), time to peak force (TTP) and time to relaxation (TTR) were determined at 37°C and 0.2–2 Hz pacing frequency. F1Hz/F0.5Hz and F2Hz/F0.5Hz served as measures of FFR, intracellular cardiomyocyte t-tubule distance (ΔTT) as measure of t-system remodeling. Protein levels of SERCA2, NCX1, and PLB were quantified by immunoblotting. F1Hz/F0.5Hz (R2 = 0.82) and F2Hz/F0.5Hz (R2 = 0.5) correlated negatively with ΔTT, i.e., samples with severe t-system loss exhibited a negative FFR and reduced myocardial wall tension at high pacing rates. PLB levels also predicted F1Hz/F0.5Hz, but to a lesser degree (R2 = 0.49), whereas NCX1 was not correlated (R2 = 0.02). CD90 correlated positively with ΔTT (R2 = 0.39) and negatively with SERCA2/PLB (R2 = 0.42), indicating that both the t-system and SERCA activity are important for contraction kinetics. Surprisingly, ΔTT was not associated with TTP (R2 = 0) but rather with TTR (R2 = 0.5). This became even more pronounced when interaction with NCX1 expression was added to the model (R2 = 0.79), suggesting that t-system loss impairs myocardial relaxation especially when NCX1 expression is low. The degree of t-system remodeling predicts FFR inversion and contraction slowing in failing human myocardium. Moreover, together with NCX, the t-system may be important for myocardial relaxation.
CRIS-Team Scopus Importer:2020-04-14
Keywords: cardiac excitation-contraction coupling; cardiac remodeling; force frequency relationship; heart failure; human heart; transverse tubular system

T-tubule loss in rat and human cardiomyocytes aggravates the effects of reduced SERCA activity on Ca2+ release - Fiegle, Dominik; Volk, Tilmann; Seidel, Thomas (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07

Twenty-four hours preservation of hearts prior to cardiomyocyte isolation to reduce the number of experimental animals - Pfeilschifter, Benedikt; Seidel, Thomas; Volk, Tilmann (ACTA PHYSIOLOGICA, 2022)
CRIS-Team WoS Importer:2022-10-07